Cestus Responds to Aethiopissa - Whalen, Robert (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
Yale Osborn MS. b 197 includes a neglected witness, one of six, to George Herbert’s “Aethiopissa ambit Cestum Diuersi Coloris Virum,” followed by the only known copy of a twenty-two-line reply, “Cesti ad Aethiopissam Responsio.” This latter cannot be said with any certainty to be Herbert’s; it is nevertheless a fascinating rejoinder to perhaps the most un-Herbertian of his poems. This paper provides edited texts, original translations, and apparatus; a description of the manuscript; and consideration of arguments for and against attributing the new poem to Herbert.